Bilobed right lung: a case of absent horizontal fissure - Chauhan, Ankita; Yadav, Suman; Patiyal, Nitin (International Journal of Research in Medical Sciences, 2021)
The human lungs are organs of respiration present in the greater part of thoracic cavity on each side of heart in the mediastinum resting on diaphragm. The right lung is classically divided into three lobes namely superior, middle and inferior by the oblique and horizontal fissures. The left lung is divided into superior and inferior lobes by a single deep oblique fissure. The fissures help in expansion of lungs during respiration. During the routine dissection of thoracic region of human cadaver, bilobed right lung with absent horizontal fissure was observed. The right lung was divided into superior and inferior lobe by a single oblique fissure. The left lung had normal anatomy in this case. The variations in the fissures and lobar pattern of lungs are common and are due to altered developmental process during intrauterine life. The anatomical knowledge of these disparities in fissures is important for clinicians prior to performing any pulmonary surgical procedures and to prevent postoperative complications.